Clinical Evaluation Of Ashmarihar Kasaya In The Management Of Urolitiasis (Mutrashmari) - Ranga, Vinod; Ranga, Sneh (International Research Journal of Ayurveda & Yoga, 2022)
Urolithiasis is the most common urinary tract problem affecting people globally. Efforts have been made continuously since past, for a safe & effective treatment for this alarming disease. The best and latest modern treatment for this disease is invasive surgery which requires hospital stay, pain and post-operative complications. In this context an Ayurvedic classical formula Ashmarihar Kasaya (Siddhayoga Samgraha Ch.18) is described as an effective drug in management of urolithiasis (mutrashmari). So a study was performed on account of above statement. The result was assessed by using a series of parameter and it was found that Ashmarihar Kasayais highly significant in relieving most of the signs & symptoms. Also, the drug is found effective in removal of small (≤ 5mm) stones and reduce the size of big (6-10mm) stones present in ureter, bladder and kidney.